Hematological values and body, heart and liver weights of male and female broiler embryos of young and old breeder eggs - Morita, V. S. [UNESP]; Boleli, I. C. [UNESP]; Cargnelutti Filho, A. (Fundação APINCO de Ciência e Tecnologia Avícolas, 2009)
This study analyzed broiler breeder age (29 or 60 wk-old) effects on physical characteristics of eggs (initial mass, mass loss, volume, diameter, surface area and density) and of eggshells(weight, volume, thickness, conductance, and porosity ), as well as the influence of embryo sex on hematological parameters and body, liver and heart weights during incubation (at days 13, 15, 18 and 21). Physical parameter values were lower in 29-wk-old broiler breeder eggs than those of 60-wk-old breeders, except for relative eggshell weight, which was higher. In both male and female embryos, erythrocytic parameters and the body, liver, and heart weights increased during the incubation. The embryos and their organs were heavier when derived from 60-wk-old breeder eggs as compared to 29-wk-old breeder eggs. At hatching, hematocrit values were higher in males than in females. Thrombocytes were the most frequent leukocytes in the blood. Thrombocyte percentage decreased and lymphocyte percentage increased during the last days of incubation. The results showed maternal age influence only on body, heart and liver weights, focal sex-related influence the hematocrit at hatching, and temporal effect of incubation on body and organ weights, as well as on red blood cell count, hematocrit, hemoglobin, plasma glucose, and lymphocytes, which increased during the incubation period, while mean corpuscular volume and thrombocyte values decreased.
Keywords: Blood parameters; breeder age; Embryos; eggshell porosity and conductance; sex